Perspectives of the Community and Bureaucrats Regarding Relocation of Capital from Jakarta to Kalimantan - Raizaada Balqsit Nurhalisa; Muhammad Eko Atmojo (KEMUDI : Jurnal Ilmu Pemerintahan, 2024)
The process of moving the capital city from Jakarta to IKN is still ongoing. Development and land acquisition continue to be carried out to accelerate the transfer process so that it can be completed this year. But in the midst of the ongoing relocation process, some individuals are still voicing their opinions on the relocation of the capital. The opinions expressed are diverse and from various circles. Therefore, the purpose of this research is to find out the perspectives of the community and bureaucrats on the transfer of the capital from Jakarta to IKN. This research uses qualitative research using indirect quotes and IoT. The research technique is used as a review to write a literature review. In addition, the author also used VOS viewers and NVivo 12 Plus to visualize research data for the journal. As a researcher, the author first explains what factors underlie the transfer of the capital from Jakarta to IKN then the author will describe what are the impacts caused by the transfer of the capital from Jakarta to IKN. In this study we used an indicator, namely the perspective theory of Joel M Charon, then from this indicator two parameters were produced, namely positive perspectives and negative perspectives. After that the author explains some responses from various parties related to the relocation of the capital and concludes which perspectives are often discussed along with suggestions or solutions that can be taken.